Programa um computador por aluno: política pública e políticas de subjetivação - Cazonatto, Camilo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Starting from an inquire on the public policy entitled One Computer per Student Program (PROUCA) [Programa Um Computador por Aluno], the present study sought to assess the biopolitics strategies implemented as government technologies nowadays. Taking the clashing in relationships between the actors on the international setting as its premise, essay's discussion focuses on the possibilities of resistance and capture, trough the assertions made by discourses of truth on digital inclusion and the need to improve the learning process by the use of information and communications technology in the classroom. A critical reading of official documents that gave support to the Federal Government in the adoption of PROUCA, as well as inquiries on the official wiki of the NGO responsible for the dissemination of the methodology adopted in the implementation of this policy, enabled the recognition of the actors involved in it, their roles played through the exercise of power, and the conclusion that these persistent disputes are directly intertwined in the existing social, political and economic regime.

A investigação delineada neste trabalho parte da análise da política pública educacional denominada “Programa Um Computador por Aluno” – PROUCA. A presente pesquisa buscou questionar as estratégias biopolíticas agenciadas enquanto tecnologias de governo na contemporaneidade. Tendo como premissa o embate nas relações entre os atores dispostos em um cenário internacional, as discussões foram circunscritas às possibilidades de resistência e captura, a partir da emissão de discursos de verdade acerca da inclusão digital e da necessidade de tornar mais eficiente o processo de aprendizagem a partir do uso de novas tecnologias de informação e comunicação em sala de aula. A leitura crítica de documentos oficiais, que deram sustentação ao Governo Federal na adoção do PROUCA, bem como as indagações junto à wiki oficial da ONG, responsável pela disseminação da metodologia adotada na implantação dessa política, possibilitaram o reconhecimento dos atores envolvidos, os respectivos papéis que cumpriram mediante o exercício do poder e a conclusão de que essas constantes disputas estão diretamente imbricadas no regime social, político e econômico vigente.
One computer per student program: public policy and subjectivation policys
Keywords: Tecnologias; Inclusão Digital; Política Pública; Biopolítica; Poder; Technologies; Digital inclusion; Public policy; Biopolitics; Power